2014
DOI: 10.1007/s11664-014-3547-x
|View full text |Cite
|
Sign up to set email alerts
|

Forming Free Bipolar ReRAM of Ag/a-IGZO/Pt with Improved Resistive Switching Uniformity Through Controlling Oxygen Partial Pressure

Abstract: Bipolar resistive switching properties of Ag/a-IGZO/Pt structure resistive random-access memories (ReRAMs) were investigated. The amorphous In-GaZn-O (a-IGZO) films were prepared by a radio frequency magnetron sputtering system at room temperature in mixed gas ambient of argon (Ar) and oxygen (O 2 ). The oxygen partial pressures during sputtering deposition were varied from 0% to 17% to engineer defects in an a-IGZO layer. When the oxygen partial pressure increased to 17%, forming-free bipolar resistive switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…The different conduction behaviors in the HRS and LRS suggest that the high conductivity in On-state cell is likely to be a confined effect rather than a homogenously distributed one. The similar IeV characteristics had been observed in the Ag/a-IGZO/Pt ReRAM structure reported in our previous work [12]. Ohmic and SCLC current are bulk dominated mechanisms.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The different conduction behaviors in the HRS and LRS suggest that the high conductivity in On-state cell is likely to be a confined effect rather than a homogenously distributed one. The similar IeV characteristics had been observed in the Ag/a-IGZO/Pt ReRAM structure reported in our previous work [12]. Ohmic and SCLC current are bulk dominated mechanisms.…”
Section: Resultssupporting
confidence: 89%
“…In addition, the temperature coefficient of resistance of the filaments corresponds with the value for Ag/a-IGZO/Pt structure reported in our previous work [12], which is 6.9 Â 10 À3 K À1 . The results suggest that the filaments are composed of Ag in metallic states due to the diffusion of the top electrode under a bias voltage.…”
Section: Resultssupporting
confidence: 74%
“…The memory windows reached 10 5 within 100 endurance cycles. Such a switching ratio is orders of magnitude higher than that of the previously reported IGZO-ReRAMs [25]- [27], [38]- [40]. Furthermore, the memory window of our ReRAMs remains nearly constant during a Pengfei Ma, Guangda Liang, Yiming Wang, Yunpeng Li, Qian Xin, Yuxiang Li, and Aimin Song, Senior Member, IEEE High-performance InGaZnO-based ReRAMs w retention test of 10 5 s. The conduction and switching mechanism was also analysed by examining different possible models.…”
Section: Introductionmentioning
confidence: 53%
“…Our previous work demonstrated that IGZO TFTs are suitable for future wearable and other low-power electronics because of their high yield and low operation voltages [19], [20]. IGZO films have recently been found to exhibit resistance switching properties [25]- [29]. Liu et al demonstrated an integration of IGZO TFT and ReRAMs to form a one-transistor-one-resistor (1T1R) configuration [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation